Analyzing the Concept of Basyar as Human: A Semantic Study of The Qur’an - Latief, Mohammad; Kusuma, Amir Reza; Nurrohman, Muqit; Zarkasyi, Hamid Fahmy (AL-TAHRIR, 2025)
This study investigates the semantic implications of the term basyar as it pertains to the concept of humanity in the Qur’anic discourse. The research arises from the observation that the Qur’an employs a range of lexical choices to denote human beings, including nās, al-insān, basyar, banī ādam, al-insu, and al-marʾu, each carrying distinct contextual and conceptual connotations. The diversity of these terms reflects the Qur’an’s nuanced portrayal of human nature across different dimensions and circumstances. Focusing specifically on basyar, this study aims to delineate the unique aspects embedded within this term and how it informs the Islamic understanding of human identity. Methodologically, this is a qualitative literature-based study employing documentary analysis of primary sources such as the Qur’an and classical tafsīr works, including Tafsīr al-Qur’ān al-‘Aẓīm by Ibn Kathīr, Tafsīr al-Marāghī by Ahmad bin Musthafa al-Marāghī, Mafātīḥ al-Ghayb by Fakhruddīn al-Rāzī, and Rūḥ al-Maʿānī by Shihābuddīn al-Ālūsī, among others. The findings suggest that while the concept of basyar aligns closely with the general notion of humanity, it conveys an elevated understanding marked by specific virtues. The study identifies five defining characteristics of human beings within the basyar framework: (1) prophethood as a human function, (2) creation from earthly elements, (3) the cognitive and existential dimension of basyariah, (4) the social interaction between genders, and (5) the inevitability of death as part of divine ordinance.